Peiminine Enhances Doxorubicin Cytotoxicity and Downregulates hsa-miR-106a-5p and hsa -miR-181a-5p in Human Gastric Adenocarcinoma Cells - Shirin Hedayati; Hossein Soltanzadeh; Hadi Esmaeili Gouvarchin Ghaleh; Zahra Hojjati Bonab; Akbar Ghorbani Alvanegh (Advanced Biomedical Research)
Background: Gastric cancer (GC) is a prevalent and deadly cancer worldwide. Chemotherapy is the primary treatment, but some patients use herbal remedies, such as Peiminine from Fritillaria walujewii, for palliative care. Cancer cells can affect the expression of noncoding RNAs, like microRNA, which can then influence the expression of genes. This research aims to study the effects of Peiminine on Doxorubicin cytotoxicity and detect the expression levels of hsa-miR-106a-5p and hsa-miR-181a-5p in AGS human gastric adenocarcinoma cells. Materials and Methods: AGS cells were cultured and treated with different concentrations of Peiminine. An MTT assay was performed to determine the concentration of Peiminine required to prohibit 50% cell growth (IC50) and the cell viability percentage of the AGS cell line. The percentage of AGS cell line apoptosis was determined using acridine orange (AO) and ethidium bromide (EtBr). Finally, molecular studies were conducted to compare hsa-miR-106a-5p and hsa-miR-181a-5p expression in the control and treated groups. Results: According to the study, Peiminine has been found to enhance the cytotoxicity of Doxorubicin, which reduces cell viability and increases apoptosis in the AGS cell line. Furthermore, the study also indicates that the AGS cell line treated with Peiminine shows lower expression of hsa -miR-106a-5p and hsa -miR-181a-5p compared to the control group that was not treated. Conclusion: Peiminine enhances Doxorubicin’s effectiveness, inhibits AGS cell line growth, and reduces miRNA expression. Further research is needed for potential use as a supplementary GC treatment.